Investigation of 1d Photonic Crystal Based on Nano-porous Silicon Multilayer for Optical Filtering - Chi, Do Thuy; Huy, Bui; Van, Nguyen Thuy; Hoi, Pham Van (Communications in Physics, 2011)
We present the fabrication, simulation, and measurements of 1D photonic crystal based on nano-porous silicon multilayer designed as an optical interference filter. Using electro-chemical etching with timely repeat steps of applied current densities, we fabricated a multilayer structure composed of alternating high- and low-index layer which achieved 90% power reflectivity at wavelength range of 1400-3000 nm. The simulation is relying on the Transfer Matrix Method (TMM) to design and predict the optical properties of nano-porous silicon multilayer as well as the relation between anodization parameters with reflection spectra. The measured reflection and transmission spectra of the nano-porous silicon multilayer show good agreement with simulation. This technique could provide a convenient and economical method to produce filters, cavities, and graded-index dielectric waveguides in the future.